Теория управления учебник для вузов - Васильев Ю. В. Юрий Викторович; Парахина В. Н. Валентина Николаевна; Ушвицкий Л. И. Лев Исакович; Воронцова Г. В.; Калюгина С. Н.; Парахина В. Н.; Ушвицкий Л. И. (Москва, Финансы и статистика, 2008)
Авт. указаны на обороте тит. л.